TYPE II EXTERNAL FIXATOR TO STABILIZE RADIAL FRACTURE IN ADULT HORSE - CASE REPORT - Dória, Renata Gebara Sampaio; de Freitas, Silvio Henrique; Mendonça, Fábio de Souza; Pires, Marco Aurélio Molina; dos Santos, Marcelo Diniz; de Camargo, Lázaro Manoel (Brazilian Journal of Veterinary Medicine, 2010)
ABSTRACT. Dória R.G.S., Freitas S.H. de, Mendonça F. de S., Pires M.A.M., Santos M.D. dos & Camargo L.M. de. [Type II external fixator to stabilize radial fracture in adult horse - Case Report]. Fixador externo tipo II na estabilização de fratura de rádio em equino adulto - Relato de caso. Revista Brasileira de Medicina Veterinária, 32(1):11- 15, 2010. Departamento de Clínica e Cirurgia, Faculdade de Medicina Veterinária, Universidade de Cuiabá, Residencial Villas Boas, Casa 26, Avenida Antártica, 788, Ribeirão da Ponte, Cuiabá, MT 78040-500, Brasil. E-mail: renata-doria@uol.com.br A case of complete diafisary radial fracture in an adult horse is reported. It was used type II external fixator to reduce and stabilize it. Even though the literature discourage corrective surgeries to this type of fracture in adult animals, this study reports a successful case in anesthetic recovery and efficient immobilization of the fracture site characterized by quadrupedal positioning and locomotion with support of the affected forelimb.